2016
DOI: 10.1038/srep38150
|View full text |Cite
|
Sign up to set email alerts
|

UV Degradation and Recovery of Perovskite Solar Cells

Abstract: Although the power conversion efficiency of perovskite solar cells has increased from 3.81% to 22.1% in just 7 years, they still suffer from stability issues, as they degrade upon exposure to moisture, UV light, heat, and bias voltage. We herein examined the degradation of perovskite solar cells in the presence of UV light alone. The cells were exposed to 365 nm UV light for over 1,000 h under inert gas at <0.5 ppm humidity without encapsulation. 1-sun illumination after UV degradation resulted in recovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(155 citation statements)
references
References 67 publications
3
143
1
Order By: Relevance
“…In the case of the FMC module, a reverse behaviour is noted and the module shows enhanced performance in the afternoon and this appears to be driven by changes in FF, and to a lesser extent VOC. This is likely to be due to the filling of traps by the photogenerated carriers as the device is light soaked during the course of the day, as also observed by Shao et al [23].…”
Section: Diurnal Performancementioning
confidence: 56%
See 1 more Smart Citation
“…In the case of the FMC module, a reverse behaviour is noted and the module shows enhanced performance in the afternoon and this appears to be driven by changes in FF, and to a lesser extent VOC. This is likely to be due to the filling of traps by the photogenerated carriers as the device is light soaked during the course of the day, as also observed by Shao et al [23].…”
Section: Diurnal Performancementioning
confidence: 56%
“…A number of papers have considered the partial recovery of solar cell performance under dark conditions [24]- [26]. The root cause of the reversible degradation has not decisively been attributed to a single cause, but is likely to be related to either metastable defect or trap changes which are reversed overnight, or reversible changes in ion redistribution under illumination [23].…”
Section: Diurnal Performancementioning
confidence: 99%
“…Originally this effect has been entirely attributed to photodegradation of TiO2 52 . However, in a most recent study, it was shown that under strictly controlled environmental conditions, the initial phase of the UV induced degradation of the PVSC performance is optically reversible through illumination with the solar spectrum photons 53 . It was also shown that a permanent, irreversible degradation associated with photoelectrochemical reactions in TiO2 occurs for the UV exposure times longer than 200 hrs.…”
Section: Ultraviolet Light Induced Perovskite Solar Cell Degradamentioning
confidence: 99%
“…However, these losses can be $40% recoverable over 10 cycles by alternating between UV and AM1.5G illumination. 33 Note that while we define UV light as an intrinsic parameter, we recognize that it could be considered extrinsic given the option of using UV-blocking encapsulant layers. 12 The substantial variation in performance as a function of illumination conditions urges the realization of supervised and unsupervised ML on perovskite thin films (prior to full device development), where PL measurements are sufficient to determine the conditions for radiative recombination recovery.…”
Section: The Need For Research In Hoip Dynamics and Recoverymentioning
confidence: 99%